Web accessibility in Chile: evaluation of an educational portal (Educación y Tecnología, 2022)
This mixed research with a quantitative predominance aims to establish the relation that exists between the design of inclusive web technologies with the current legislation in Chile. Current regulations are analyzed, based on the Web 2.0 Accessibility Guideline of the Web Accessibility Initiative of the World Wide Web Consortium Level AA. The Educarchile portal is evaluated in two moments with 4 automatic online tools, then a manual evaluation was applied to verify the preliminary results and finally the Usability Test was applied in a person with visual impairment. Basic design problems were evident, such as the absence of alternative texts in required elements and the absence of a Site Map, therefore it is considered a non-accessible site, but with adequate usability, as it does not present any inconvenience in the experience of user navigation.
Keywords: Education; accessibility; inclusion; usability; Internet